RECENT TENDENCIES IN GERMAN BUSINESS ECONOMICS. - Schranz, A. (The Accounting Review, 1937)
The science of business economics is looked upon in the German-speaking countries as a particular and largely independent branch of the general science of economics. From a broad standpoint it has the same objective and content as American business organization and administration. But upon closer examination it is seen to be more theoretical, more pretentious of being an independent, compact science parallel to economics and more thoroughly permeated throughout with accounting. In its modern phase German business economics is of very recent origin, having begun hardly more than fifteen years ago. From the standpoint of its complete history, however, it must be considered to have had a fairly early origin in as much as it first appeared in full bloom during the seventeenth and eighteenth centuries. During that period English and French Mercantiism and Physiocratism were at their height. In place of the ideas associated with those two schools of economic thought, however, there were present on German soil the two main early stages of German business economics "cameralism" and what may be translated as the "science of trade."